(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Student Portal is a web portal where all information and all services that students need can be found in one place. It might be one of the best ways to use technology for the benefit of the students. The aim of this project is to build a system that helps the student to see their grades, request documents, print their Certificate of Registration, and make payments online anytime they want. A student portal is to enhance the student experience, improve communication and collaboration, streamline administrative processes, and make their life easier. As a result, the study eliminates the problems and issues in the school management system. The students save a lot of time; instead, they go to school to do some things regarding school. In addition, a multi-purpose student profile that allows access from both mobile and desktop devices was introduced as a result of the deployment of succession planning, which also made learning and development programs more central to every school. This project will enhance the functionality and usability of the Bestlink College of the Philippines’ student portal. In this project, the system integration will enable all the information needed to adequately measure each student’s learning and transaction development. Additionally, a central student profile enables information like timetables, password changes, and more, including announcements, effortlessly through a computer or mobile browsing.